Project Management in Design and its Impact on User Experience UX (Comprehensive Journal of Science, 2026)
This study investigated the impact of project management in interior design on the quality of the user experience (UX), given that contemporary interior design is no longer limited to aesthetic aspects but has rather evolved into an integrated system combining function, management, psychological comfort, and operational sustainability. The study aimed to analyze the relationship between the efficiency of administrative governance in design projects and the level of final user satisfaction across various spatial environments. The researchers adopted a descriptive, analytical, and deductive approach, reviewing recent literature and applied studies linking project management, interior design, and user experience, while systematically analyzing the lifecycle stages of design projects—from the inception of the design brief to post-occupancy evaluation.The findings revealed a direct, statistically and qualitatively significant correlation between the application of modern management methodologies—particularly Agile and Lean management—and the elevation of design output quality alongside the optimization of the functional and environmental performance of internal spaces. Furthermore, the results demonstrated that poor timeline scheduling and deficient financial budgeting invariably lead to a decline in the execution quality of finishes and materials, which directly and adversely affects the physical and psychological comfort of the user. Consequently, the study recommended the vital integration of modern management sciences into the curricula of interior design departments at higher institutes, the activation of rigorous control tools over materials procurement, and the institutionalization of the post-occupancy evaluation phase within the lifecycle of design projects to enhance the internal environmental quality and achieve a more efficient, sustainable user experience.
Keywords: Project Management – Interior Design – User Experience (UX) – Agile Management – Administrative Governance – Interior Space Quality.